Impact of donor lung pathogenic bacteria on patient outcomes in the immediate post‐transplant period. Issue 6 (21st September 2018) - Ahmad, Omar; Shafii, Alexis E.; Mannino, David M.; Choate, Radmila; Baz, Maher A.
Abstract: Background: Patient outcomes post‐lung transplant remain inferior to other types of solid organ transplantation. We investigated whether the presence of potentially pathogenic bacteria (PPB) in donor lung bronchial cultures was associated with adverse outcomes postoperatively. Methods: All patients who underwent lung transplantation between August 2015 and April 2017 at the University of Kentucky Medical Center were retrospectively reviewed. Retransplants, patients with bronchiectasis (including cystic fibrosis), and individuals who received organs from donation after cardiac death (DCD) donors were excluded. The remaining subjects were separated into two groups: individuals whose donor bronchial cultures grew PPB, and those whose cultures either returned negative for PPB or were sterile. 30‐day mortality rates as well as the incidence of grade 3 primary graft dysfunction (PGD) and acute kidney injury (AKI) at both 24 and 72 hours post‐transplant were calculated. The duration of mechanical ventilation postoperatively was also recorded. Results: Thirty two subjects comprised the study population. 20 patients (63%) had growth of PPB on donor cultures, while 12 (37%) did not. Patients with PPB had a significantly greater number of days on the ventilator postoperatively compared to those with no PPB (mean = 11.3 and median = 5.0 vs mean = 5.8 and median = 3.0, respectively, P = 0.0232). Subsequent regression analysis revealed this association to not be influenced by recipient lung allocation score (LAS), donor age, donor smoking history, recipient mean pulmonary artery pressure (mPAP) value, and/or use of cardiopulmonary bypass at the time of transplantation. Neither 30‐day survival nor incidence of Grade 3 PGD and AKI at 24 or 72 hours post‐transplant differed between the two groups ( P > 0.05). Conclusion: The recovery of PPB in donor lung cultures was associated with a longer duration of mechanical ventilation postoperatively in lung transplant recipients.